Causal association between Parkinson’s disease and cancer: a bidirectional Mendelian randomization study - Tang, Chunyan; Fu, Ping; Lin, Liangqing; Zhou, Hui; Huang, Yunjun; Li, Yang; Zhao, Sijun (Frontiers in Aging Neuroscience, 2024)
BackgroundPrevious observational research has indicated a correlation between Parkinson’s disease (PD) and multiple cancers; but the causality remains unclear. Thus, we utilized Mendelian randomization (MR) analysis to explore the potential causal link between PD and various cancers.MethodsWe conducted a bidirectional two-sample Mendelian randomization (TSMR) of genetic variants associated with PD and 14 types of cancers. Summary statistics on PD and 14 types of cancers were obtained from the International Parkinson’s Disease Genomics Consortium and the study by Sakaue et al. The primary method employed was inverse variance weighted (IVW), complemented by multiple sensitivity analyses to evaluate heterogeneity and pleiotropy. The false discovery rate (FDR) was employed to control the false positive rate of multiple hypothesis testing.ResultsFollowing rigorous sensitivity analyses and corrections, our findings revealed suggestive associations between PD and certain cancers. We observed that PD decreases the risk of gastric cancer and colorectal cancer (OR = 0.936, 95% CI = 0.881–0.995, p = 0.034, P FDR = 0.239; OR = 0.955, 95% CI = 0.912–0.999, p = 0.046, P FDR = 0.215), while increasing the risk of breast cancer (OR = 1.043, 95% CI = 1.004–1.084, p = 0.029, P FDR = 0.402). Notably, we found no evidence supporting a reverse causal relationship. Additionally, in the reverse pathway, skin cancer demonstrated a suggestive causal relationship with PD (OR = 0.913, 95% CI = 0.857–0.973, p = 0.005, P FDR = 0.066).ConclusionOur MR analysis provides evidence supporting unidirectional suggestive causal relationships between PD and certain cancers. These findings enrich our comprehension of the intricate interplay between PD and cancer, warranting further investigation into the underlying biological mechanisms.